Optimizing CMV therapy: Population pharmacokinetics and Monte Carlo simulations for letermovir and maribavir dosage - Yeleen Fromage; Hamza Sayadi; Sophie Alain; Pierre Marquet; Gilles Peytavin; Jean-Baptiste Woillard (PLoS ONE, 2025)
Purpose This study seeks to reassess and enhance the dosing strategies of letermovir and maribavir for treating cytomegalovirus (CMV) infection, aiming to propose adjustments that could improve therapeutic effectiveness. Methods Pre-existing population pharmacokinetic models were used alongside Monte Carlo simulations to evaluate the dosing strategies of letermovir and maribavir in CMV treatment. The simulations assessed the probability of target attainment for current and alternative dosing regimens, including scenarios with missed doses. Results For letermovir, a loading dose on the first day of treatment initiation appeared more effective than the current strategy without a loading dose. Additionally, in cases of missed doses, doubling the dose upon resumption was more effective than returning to the normal dosage. For maribavir, the current 400mg BID regimen only covers the lower end of the inhibitory concentration 50 range, suggesting a potential benefit from increasing the doses. Simulations indicated that for missed doses, all tested regimens only covered the lower range of inhibitory concentrations, but the current strategy of resuming the normal dosage provided the lowest chances of target attainment. Conclusion Our findings suggest a strong rationale to reconsider and potentially modify the approved dosing guidelines for letermovir and maribavir in CMV treatment. Adjusting dosing regimens, including the use of loading doses and increased doses after missed doses, could enhance treatment outcomes by ensuring higher probabilities of achieving therapeutic targets and better managing missed doses.